Origin of resistance to pyrethroids in the redlegged earth mite (Halotydeus destructor) in Australia: repeated local evolution and migration. Issue 2 (1st July 2019) - Yang, Qiong; Umina, Paul A; Rašić, Gordana; Bell, Nicholas; Fang, Jichao; Lord, Alan; Hoffmann, Ary A
Abstract: BACKGROUND: Halotydeus destructor is a major pest of crops and pastures across southern parts of Australia. This invasive mite has been chemically controlled for over 50 years, but resistance to synthetic pyrethroids and organophosphates is developing. Understanding processes behind the emerging resistance is important for effective management efforts. We undertook a ddRAD pool‐sequencing approach to analyse genome‐wide single nucleotide polymorphism variation in H. destructor population samples at two scales: local resistance across a set of fields, and regional resistance across their Australian range, along with toxicology bioassays to screen for pyrethroid resistance. RESULTS: Spatial patterns of genomic variation and resistance at a local scale indicated that genetic similarity among samples was more closely correlated with distance along roads and fence‐lines than with straight‐line geographic distance. This pattern was particularly strong in resistant samples, which were also more related than susceptible samples, suggesting local spread of resistance within an area after it emerged. By contrast, regional data suggest resistance has emerged repeatedly within parts of Australia. Our de novo annotation of the H. destructor draft genome sequence and Bayesian analysis identified several candidate loci strongly associated with population‐level resistance to pyrethroids, located in genomic regions that code for transmembrane transport and signalling proteins that have previously been linked to insecticide resistance in other arthropods. CONCLUSION: Our findings highlight multiple independent evolutionary events leading to resistance in H. destructor, and demonstrate the utility and cost‐effectiveness of a cross‐population, genome‐wide association study to reveal processes underlying adaptive evolution in a non‐model invasive species. © 2019 Society of Chemical Industry Abstract : Pyrethroid resistance in redlegged earth mite presents a substantial challenge to agriculture across southern Australia. Understanding the evolutionary processes driving the emergence of resistance is critical for effective management strategies.